Organizational commitments to equality change how people view women's and men's professional success - Kristin Kelley; Lena Hipp; Paula Protsch (Scientific Reports, 2024)
To address women's underrepresentation in high-status positions, many organizations have committed to gender equality. But is women's professional success viewed less positively when organizations commit to women's advancement? Do equality commitments have positive effects on evaluations of successful men? We fielded a survey experiment with a national probability sample in Germany (N0.167em=0.167em3229) that varied employees' gender and their organization's commitment to equality. Respondents read about a recently promoted employee and rated~how decisive of a role they thought intelligence and effort played in getting the employee promoted from 1 “Not at all~decisive” to 7 “Very~decisive” and the fairness of the promotion from 1 “Very unfair” to 7 “Very fair.” When organizations committed to women's advancement rather than uniform performance standards, people believed intelligence and effort were less decisive in women's promotions, but that intelligence was more decisive in men's promotions. People viewed women's promotions as least fair and men's as most fair in organizations committed to women's advancement. However, women's promotions were still viewed more positively than men's in all conditions and on all outcomes, suggesting people believed that organizations had double standards for success that required women to be smarter and work harder to be promoted, especially in organizations that did not make equality commitments.
Keywords: 320